Using technology to facilitate process writing and interaction among adult students (2008)
This article deals with how through the innovative use of word processing software, process writing and interaction can be fostered among students. A description of the context where the technology is implemented is first laid out, followed by a review of the literature concerning process writing and technology based principally on Pennington’s (1996) model. Pennington’s (1996) model is then expanded on inasmuch as the way in which collaboration around the computer (group and pair work) and through the computer (e-mail, chat, blogs, and forums) can give rise to interaction among students and, therefore, language learning and more autonomous students. Finally, a lesson plan is presented where stages and examples are given showing how technology can be implemented in practice. Key words: Technology, process writing, word processing, interaction, collaboration, autonomy, metacognitive control Este artículo muestra cómo, a través del uso innovador del software para procesar textos, se puede fomentar la escritura por procesos y la interacción entre los estudiantes. En primer lugar se describe el contexto donde se implementará la tecnología, seguido por una revisión de la literatura relacionada con la escritura por procesos y la tecnología basada principalmente en el modelo de Pennington (1996). Luego se expande dicho modelo teniendo en cuenta la colaboración alrededor del computador (trabajo en grupo y en pareja) y cómo a través del computador (correo electrónico, chat, blogs, y foros) se puede generar interacción entre estudiantes, en el aprendizaje de un idioma extranjero y por ende, estudiantes más autónomos. Finalmente, se presenta un plan de clase donde se ilustran las etapas y los ejemplos para demostrar cómo se puede, en la práctica, implementar la tecnología. Palabras clave: Tecnología, escritura por procesos, procesamiento de textos, interacción, colaboración, autonomía, control metacognitivo